Low perioperative hemoglobin as an independent detrimental predictor of functional outcome after basal ganglia hemorrhage: development and validation of a composite prognostic model - Li, Xia; Zhang, Lijun; Yang, Zhikun; Ding, Jian; Yu, Yanfei; Yang, Shuo; Duan, Feng; Dong, Yi (Frontiers in Human Neuroscience, 2025)
BackgroundBasal ganglia hemorrhage (BGH) is a life-threatening neurosurgical emergency associated with substantial mortality and disability. Accurate postoperative prognosis assessment remains challenging due to multifactorial influences. Hemoglobin (HB), as the key determinant of oxygen delivery, may play a critical role in neurological recovery, yet the prognostic significance of perioperative HB fluctuations in BGH has not been fully elucidated.MethodsA retrospective cohort of 213 surgically treated BGH patients from 2020 to 2023 was analyzed. Perioperative HB indices, including preoperative (Pre-HB), postoperative (Post-HB), and mean HB (Mean-HB) levels, were evaluated alongside clinical data. Functional outcome at 6 months was determined based on the modified Rankin Scale (mRS). Least absolute shrinkage and selection operator (LASSO) regression together with multivariate logistic regression models were utilized to screen for independent risk variables, followed by construction of a composite predictive model. Model discrimination, calibration, and evaluation of the model’s clinical applicability were conducted using receiver operating characteristic (ROC) analysis, calibration plots, and decision curve analysis (DCA).ResultsPatients with poor prognosis exhibited significantly lower Pre-HB, Post-HB, and Mean-HB levels (all P < 0.05). Multivariate analysis confirmed these variables as independent predictors of adverse outcome. The proposed model provides a practical and data-driven tool that demonstrated good predictive performance (AUC = 0.84) in a single-center retrospective cohort. Calibration and DCA demonstrated good consistency and potential clinical applicability.ConclusionPerioperative declines in HB are independently associated with poor postoperative outcomes in BGH. The proposed HB-integrated model provides a reliable, dynamic tool for individualized risk prediction, facilitating precision perioperative management and optimized recovery strategies.